New boundaries of justice in a world in motion : assessing the impact of global citizens in the Irish District Court - O'Nolan, Caroline (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2011)
Although empirical research lends little support for the perceived immigration- crime nexus, it is an enduring perception. This thesis considers the impact of immigration on the Irish criminal courts. Ireland experienced sustained and substantial inward migration from 1996 to 2008. The relationship between crime and immigration in Ireland cannot be accurately determined as nationality/residency status is not recorded by most arms of the Irish criminal justice system, but, the scale and rapid increase in the committal of non-Irish nationals to Irish prisons during the period 2001 to 2007, suggest the disproportionate presence of immigrants in the Irish criminal justice system. However, this thesis highlights the administrative detention of non-Irish nationals in Irish prisons which mean that committals to prison are not an accurate indicator of the extent to which non-Irish nationals are processed by the Irish criminal justice system.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin